Establishing cleft services in developing countries: Complications of cleft lip and palate surgery in rural areas of Indonesia - Muhammad Ruslin; Lawrence Dom; Andi Tajrin; Andi Sitti Hajrah Yusuf; Syafri Kamsul Arif; Andi Husni Tanra; Keng Liang Ou; Tymour Forouzanfar; Sri Astuti Thamrin (Archives of Plastic Surgery, 2019)
Background Cleft treatment is frequently performed in Indonesia, mostly in charity missions, but without a postoperative protocol it is difficult to establish the risks and complications of cleft treatment. The present study was designed to give an overview of current cleft lip and palate treatment strategies in Indonesia and to assess the complication rates during and after surgery. Methods This prospective study evaluated anesthetic, intraoperative surgical, and short-term postoperative complications in patients undergoing primary, secondary, or corrective surgery for cleft lip and palate deformities. The population consisted of 98 non-syndromic cleft patients. The main anesthetic complication that occurred during general anesthesia was high blood pressure, whereas the main intraoperative surgical complication was excessive bleeding and the main early postoperative complication was extremely poor wound hygiene. Results In this study, there were no cases of perioperative or postoperative mortality. However, in 23 (23.4%) of the 98 operations performed, at least one perioperative complication related to anesthesia occurred. The intraoperative and early postoperative complications following cleft lip and/or palate were assessed. There was a significant difference in the complication rate between procedure types (χ 2=0.02; P<0.05). However, no relationship was found between perioperative complications related to anesthesia and the occurrence of postoperative complications (χ 2=1.00; P>0.05). Nonetheless, a significant difference was found between procedure types regarding perioperative complications and the occurrence of postoperative complications (χ 2=0.031; P<0.05). Conclusions Further evaluation of these outcomes would help direct patient management toward decreasing the complication rate.